Measurement of the n_TOF beam profile with a micromegas detector - Pancin, J. (2004)
A Micromegas detector was used in the neutron Time-Of-Flight (n_TOF) facility at CERN to evaluate the spatial distribution of the neutron beam as a function of its kinetic energy. This was achieved over a large range of neutron energies by using two complementary processes: at low energy by capture of a neutron via the 6Li(n,[alpha])t reaction, and at high energy by elastic scattering of neutrons on gas nuclei (argon+isobutane or helium+isobutane). Data are compared to Monte Carlo simulations and an analytic function fitting the beam profile has been calculated with a sufficient precision to use in neutron capture experiments at the n_TOF facility.